EVALUASI ANGGARAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM PENCIPTAAN STANDAR PELAYANAN MINIMAL (SPM) PENDIDIKAN DASAR DI KABUPATEN OGAN KOMERING ULU (OKU) - , Stephanus Hari Suprobo, Prof. Dr. Abdul Halim, MBA., Akt. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the contribution and impact of BOS funds that have been set by the government in order to meet service standards of education provided to students at the primary level. The research was conducted within the Department of Education and Culture Ogan Komering Ulu (OKU). This study is a qualitative descriptive study, with the case study method that aims to explore the contributions and impact of BOS funds that have been set by the government in order to meet service standards of education provided to students at the primary level in the district of OKU. Data were collected through interviews with the informants, the study documentation, and observation. Stages of data analysis used include data reduction, data presentation, and ended with conclusions or verification. The results showed that the factors that affect the implementation of the BOS funds budget in basic education in the district of OKU include: delays in the disbursement, the number of students, supervision system, the factor of human resources (HR), collusion and corruption, professionalism and support of information technology. The main contribution is perceived by the educational unit of useful operational availability of funds for the implementation of teaching and learning activities. Contributions of BOS funds include funds for payment of honorarium, student activities, purchase of supplies and the purchase of the student handbook. The greater the number of students, the greater the contribution of the BOS funds are perceived by the educational unit. The results obtained from different conclusion, namely the implementation of the BOS budgets has a positive impact on the creation of basic education services in accordance with the SPM, although still small in scale.